The 6 Steps of Handwashing Education - Rachmawaty M. Noer; Nurningsih Sinuraya; Septi Maisyaroh Ulina Panggabean; Zulfitri Kadri; Yuni Satriani (International Journal Of Community Service, 2021)
Washing hands with soap is part of the C lean and Healthy Behavior program in the household . Washing hands with soap is one of the preventive measures through sanitation measures by cleaning the hands and fingers using soap and water. Human hands are often the agents that carry germs and cause pathogens to pass from one person or from nature to another through direct or indirect contact. The purpose of this study was to increase the knowledge and ability to wash hands in community . The activity was carried out on May 06 and May 20, 2021 . The method used in this study is lectures and discussions as well as the practice of washing hands through video conferencing g . Participants in this activity totale d 20 people . The results obtained were increased knowledge of community and the ability to practice washing hands properly.